Synthesis and Crystal Structure of (Di-μ-dicyanamido-kN1:N5)-bis(benzimidazole)copper(II) - ZHU, BAOYONG (Asian Journal of Chemistry, 2010)
The complex (di-μ-dicyanamido-kN1:N5)-bis(benzimidazole)copper(II) with formula Cu(C2N3)2(C7H5N2)2, is reported. The crystal structure of this complex is monoclinic, space group P21/n with a = 8.622(4), b = 11.427(5), c = 9.050(6) Å, b = 107.516(2) °, C18H12CuN10, Mr = 431.92, V = 850.3(8) Å3, Dc = 1.687 g/cm3, F(000) = 438, μ = 1.315 mm-1 and Z = 2, the final R = 0.0282, WR = 0.0674 and S = 1.030 for 1549 observed reflections with I > 2s(I). It displays distorted octahedral geometry, with the Cu atom coordinated by four dicyanaide nitrile N atoms [Cu-N = 1.990(2) and 2.018(2) Å] in the basal plane, along with two monodentate benzimidazole N atoms [ Cu-N = 2.018(2) Å] in the apical positions, to form a distorted tetragonal bipyramidal geometry. The metal atoms reside on crystallographic inversion centers. Neighbouring metal atoms are connected via single dicyanamide bridges to form layers along [101] direction. Adjacent layers are then linked by N-H···H hydrogen bonds and p-p stacking interactions of the benzimidazole molecules, resulting in the formation of a three-dimensional structure.